Factors Associated With Feedback Seeking Practices of Agricultural Extension Agents in West Java, Indonesia - Darmawiredja, Mei Rochjat (1994)
The main objective of the study was to identify factors associated with feedback seeking practices of agricultural extension agents in West Java, Indonesia. This survey research employed a group self-administered questionnaire. The 254 respondents were selected randomly using multistage random sampling technique to represent 2497 agricultural extension agents on food crops throughout West Java. A five-point scale was used to measure the respondents in terms of (a) feedback seeking practices, (b) perceived uncertainty regarding the relevance of technology and its potential, (c) perceived amount of feedback received, (d) perceived credibility of the feedback source, (e) perceived importance of goal attainment, (f) perceived external propensity, (g) perceived risks of feedback seeking, (h) perceived value of feedback, (i) perceived leadership effectiveness, (j) perceived expected rewards, and (k) perceived commonness of goals, policy and implementation strategies between the research and the extension organisations. Descriptive and inferential analysis, namely frequency, Pearson's correlation, multiple regression, Z-test, and discriminant analysis have been used to analyse the data. Of the three major hypotheses, it was found that (a) extension agents who received more feedback, perceived their source of feedback as more credible, and reported more frequent contact with the specialists, were more active in feedback seeking; (b) feedback seeking was also found to be more frequently undertaken by those extension agents with a higher perception of the importance of goal attainment, external propensity, and value of feedback. In contrast, extension agents who considered feedback seeking practices as more risky were less active in feedback seeking. Feedback seeking practices were also found to be higher among extension agents with a higher perception of leadership effectiveness, expected rewards, and commonness of goals, policies and implementation strategies between the research and the extension organisations.